Actinobacteria: Source of antifungal secondary metabolites for agricultural sustainability - Vargas Hoyos , Harold Alexander (2025)
There is a need for new alternative sources of exogenous antifungals to replace those currently used in agriculture. Actinobacteria are gram-positive bacteria with a wide variety of secondary metabolites, which produce around two-thirds of all naturally occurring antibiotics in current clinical use, as well as many anticancer, anthelmintic and antifungal compounds. Consequently, these bacteria are of great importance for agricultural biotechnology, since they can be produced and applied in fields that do not promote resistance among fungi that attack plants. This review presents the research carried out regarding the identification of metabolites with fungal properties, highlighting the main species involved in the production of metabolites that are being used or could be explored in agriculture as bioproducts to promote plant health and sustainability. This review expands knowledge for future research focused on the fields of genomics, proteomics, metabolomics, synthetic biology, and ecology for the investigation of novel antimicrobial compounds to combat antifungal resistance and develop more environmentally friendly bioproducts.